Inkjet-printed porous polyaniline gel as an efficient anode for microbial fuel cells. Issue 38 (15th September 2016) - Song, Rong-Bin; Yan, Kun; Lin, Zong-Qiong; Chye Loo, Joachim Say; Pan, Li-Jia; Zhang, Qichun; Zhang, Jian-Rong; Zhu, Jun-Jie
Abstract : An inkjet-printed polyaniline gel on carbon substrate was employed as an efficient anode to remarkably improve the performance of microbial fuel cells. Abstract : Future application of microbial fuel cells (MFCs) requires a high-throughput and more convenient pathway to manufacture high-performance anodes. In this research, inkjet-printed PANI gel on carbon paper was first fabricated and then successfully employed as anodes in MFCs. Thanks to the inkjet-printing technology, such anodes can be easily produced in large quantities. Moreover, these anodes possessed good conductivity and a porous structure, as well as the ability to electrostatically interact with bacteria cells, which contributed to a 6.1-fold increase in the output power over that of the unmodified carbon paper. Taken together, our study presents a novel strategy in preparing highly scalable, high-performance MFC anodes, in promoting the practical application of MFC technology.